2018
DOI: 10.1002/marc.201700766
|View full text |Cite
|
Sign up to set email alerts
|

Medium Resolution 1H‐NMR at 62 MHz as a New Chemically Sensitive Online Detector for Size‐Exclusion Chromatography (SEC–NMR)

Abstract: A state-of-the-art, medium-resolution H-NMR spectrometer (62 MHz) is used as a chemically sensitive online detector for size-exclusion chromatography of polymers such as polymethylmethacrylate (PMMA) and polystyrene (PS). The method uses protonated eluents and works at typical chromatographic conditions with trace amounts of analytes (<0.5 g L after separation). Strong solvent suppression, e.g., by a factor of 500, is achieved by means of T -filtering and mathematical subtraction methods. Substantial improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…These are the first results from this unique IR‐spectrometer illustrating its potential to measure, for example, single end groups in a polymer chain, as this rare functionalization is of high importance in case surface absorbance is intended. The strength of this result can be further put into perspective by comparing the measured LODs for SEC‐FTIR and SEC‐MR‐NMR (measured on polystyrene in CHCl 3 ), which were reported to be 13.4 µg and 110 µg, respectively, and are reproduced in Figure . Therefore, each of the coupled SEC‐IR and SEC‐NMR techniques offers unique advantages where SEC‐FTIR and SEC‐MR‐NMR measure full spectra as a function of the polymer size at lower sensitivities and SEC‐EC‐QCL measures only over limited wavelengths at a substantially higher sensitivity.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…These are the first results from this unique IR‐spectrometer illustrating its potential to measure, for example, single end groups in a polymer chain, as this rare functionalization is of high importance in case surface absorbance is intended. The strength of this result can be further put into perspective by comparing the measured LODs for SEC‐FTIR and SEC‐MR‐NMR (measured on polystyrene in CHCl 3 ), which were reported to be 13.4 µg and 110 µg, respectively, and are reproduced in Figure . Therefore, each of the coupled SEC‐IR and SEC‐NMR techniques offers unique advantages where SEC‐FTIR and SEC‐MR‐NMR measure full spectra as a function of the polymer size at lower sensitivities and SEC‐EC‐QCL measures only over limited wavelengths at a substantially higher sensitivity.…”
mentioning
confidence: 88%
“…Comparable method development work was done by Lendl and co‐workers where they coupled liquid adsoption chromatography, LAC, to a QCL setup to measure sugars in beverages and later stand‐alone QCL setups were used to measure biological applications such as proteins in aqueous solutions, glucose levels, and multianalyte blood analysis . Analog correlation between chemical composition and molecular weight are currently conducted via SEC‐NMR indicating the needs for the acquisition of correlated information . Previous results showed that the LOD measured for the QCLS‐B was about a factor of four better than the Bruker Vertex 70 FTIR, even though a liquid nitrogen cooled MCT detector is installed on the FTIR Vertex spectrometer and a far less sensitive (balanced) LiTaO 3 detectors was used in the first prototype QCLS‐B.…”
mentioning
confidence: 99%
See 3 more Smart Citations